Evolution of Young Sex Chromosomes in Two Dioecious Sister Plant Species with Distinct Sex Determination Systems. (14th January 2019) - Martin, Hélène; Carpentier, Fantin; Gallina, Sophie; Godé, Cécile; Schmitt, Eric; Muyle, Aline; Marais, Gabriel A B; Touzet, Pascal
Abstract: In the last decade, progress has been made in methods to identify the sex determination system in plants. This gives the opportunity to study sex chromosomes that arose independently at different phylogenetic scales, and thus allows the discovery and the understanding of early stages of sex chromosome evolution. In the genus Silene, sex chromosomes have evolved independently in at least two clades from a nondioecious ancestor, the Melandrium and Otites sections. In the latter, sex chromosomes could be younger than in the section Melandrium, based on phylogenetic studies and as no heteromorphic sex chromosomes have been detected. This section might also exhibit lability in sex determination, because male heterogamy and female heterogamy have been suggested to occur. In this study, we investigated the sex determination system of two dioecious species in the section Otite s ( Silene otites and its close relative Silene pseudotites ). Applying the new probabilistic method SEX-DETector on RNA-seq data from cross-controlled progenies, we inferred their most likely sex determination system and a list of putative autosomal and sex-linked contigs. We showed that the two phylogenetically close species differed in their sex determination system (XY versus ZW) with sex chromosomes that derived from two different pairs of autosomes. We built a genetic map of the sex chromosomes and showed that both pairs exhibited a large region with lack of recombination. However, the sex-limited chromosomes exhibited no strong degeneration. Finally, using the "ancestral" autosomal expression of sex-linked orthologs of nondioecious S. nutans, we found a slight signature of dosage compensation in the heterogametic females of S. otites .